1991
DOI: 10.1093/bja/66.6.660
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of the Hypnotic Effect of Midazolam in Children: A Randomized, Doubleblind Study of Placebo and Flumazenil Administered After Midazolam-Induced Anaesthesia

Abstract: In a randomized, double-blind study, we administered placebo and flumazenil to 40 healthy Chinese boys, aged 3-12 yr, undergoing circumcision. The children received midazolam 0.5 mg kg-1 orally for premedication and 0.5 mg kg-1 i.v. during induction. After operation the patients were given 0.1 ml kg-1 of a blinded solution followed by 0.05 ml kg-1 min-1 until either they awoke or the 10-ml ampoule of solution was empty. Efficacy of antagonism of midazolam was assessed by times to eye opening and self identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Flumazenil induces rapid recovery in children who receive midazolam 0.5 mg · kg -1 orally as premedication and intravenous injection of midazolam 0.5 mg · kg -1 during induction [8]. In that study, the mean total dose of flumazenil administered to achieve awakening was 0.024 mg · kg -1 , whereas other investigators used flumazenil 0.017-0.027 mg · kg -1 to antagonize the effect of midazolam [9,16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Flumazenil induces rapid recovery in children who receive midazolam 0.5 mg · kg -1 orally as premedication and intravenous injection of midazolam 0.5 mg · kg -1 during induction [8]. In that study, the mean total dose of flumazenil administered to achieve awakening was 0.024 mg · kg -1 , whereas other investigators used flumazenil 0.017-0.027 mg · kg -1 to antagonize the effect of midazolam [9,16].…”
Section: Discussionmentioning
confidence: 95%
“…Flumazenil, a potent benzodiazepine antagonist, reverses the sedative effect of midazolam used for premedication or induction with no significant adverse effects on children [8,9]. Moreover, midazolam occasionally precipitates hostility and violence instead of tranquility, and this paradoxical phenomenon can also be reversed by flumazenil [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al 19 in a randomised, double blind study involving 40 children found that intravenous flumazenil rapidly antagonised midazolam induced hypnosis in children and was not associated with any episodes of resedation. The anxiety concerning resedation can be tackled after reviewing the pharmacokinetics of midazolam and flumazenil.…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized, double-blind, placebo-controlled study on Chinese males aged 3-12 years undergoing circumcision who received midazolam 0.5 mg/kg orally for premedication followed by 0.5 mg/kg i.v. for the induction of anaesthesia, with subsequent reversal by flumazenil, commented on the lack of resedation (39).…”
Section: General and Gynaecological Surge9mentioning
confidence: 99%